Smythe's Store and Hotel along the Yukon River at Ogilvie, ca. 1914 - Curtis, Asahel, 1874-1941 (1914)
Handwritten on verso: Ogilvie, Yukon Territory. PH Coll 519.29095 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number